Oxidative stress in SH-SY5Y cells on exposure to hydrogen peroxide (Research, Society and Development, 2022)
Oxidative stress is obtained through the formation of reactive oxygen species, which are normally produced by cell metabolism, but when produced in excess, the cell loses its ability to defend and repair, leading to damage tobiomolecules (DNA, lipids, proteins, etc). When these damages are not repaired, they end up compromising the cell's functioning, leading to death by apoptosis or necrosis. Oxidative stress is involved in neural cell death, which is a major cause of neurodegenerative diseases, including Alzheimer and Parkinson's disease. The aim of this study is to verify the action of hydrogen peroxide as a model of oxidative stress in human neuroblastoma cells. In order to analyze from which concentration a significant stress occurs in the cells and together, verify each concentration at different times of action in the cells. The experiments performed were the analysis of mitochondrial activity obtained through the MTT test, cell viability test using the Trypan blue assay, obtaining quantitative and qualitative data. It is possible to observe that from the concentration of 0.2 mM in the time of 2 hours, there is a significant decrease in the number of cells in relation to the control group, therefore, with the increase of the other concentrations in relation to time, more damage occurs in the cells.